The Influence of Self-Efficacy and Islamic Financial Literacy on the Performance of Micro, Small, and Medium-Sized Enterprises - Srisusilawati, Popon; Kurniawan, Cecep Soleh; Silviany, Irma Yulita; Mustika, Rita; Putri, Imelda; Nurfitria, Anggelia (Economica: Jurnal Ekonomi Islam, 2021)
MSMEs have long promoted a major contribution to the national economy. However, the Covid-19 pandemic has caused MSME to suffer a decline resulting in a direct effect on the economy in Indonesia. This study analyzes the influence of self-efficacy and Sharia financial literacy on MSMEs performance. The inclusion of a variable of self-efficacy is a novelty of this study. This study highlights self-efficacy and Sharia financial literacy as independent variables and business performance as the dependent variable, with the focus of research on MSMEs. The research method used is quantitative associative. Respondents from 100 MSMEs were selected using saturation sampling. Multiple linear regression was performed using IBM SPSS Statistic software. The results prove that self-efficacy and Sharia financial literacy have a simultaneous and partial positive effect on MSMEs performance.